Zeolite and Chitosan: A sustainable duo to improve sesame drought resistance - Amir Mohammad Abedi; Ali Heidarzadeh; Seyed Ali Mohammad Modarres-Sanavy (PLoS ONE, 2026)
Climate change and increasing competition for water in arid and semi-arid regions intensify moisture stress in sesame production. Deficit irrigation (DI) is therefore essential to optimize yield with limited water. This study investigated the potential of two eco-friendly amendments zeolite and chitosan to mitigate drought effects in sesame. A split-factorial experiment was conducted in a randomized complete block design with three replications at two locations (Tehran and Yazd). Irrigation treatments included optimal irrigation (I1; 50% available soil water depletion), moderate drought (I2; 65%), and severe drought (I3; 80%). Subplots received zeolite (0 and 4.5 t ha⁻ 1 ) and foliar applications of chitosan (0.4% and 0.5%) or controls. Under I1, the combined application of zeolite and 0.5% chitosan markedly improved leaf area index (LAI), grain yield, oil content, and harvest index. Antioxidant enzyme activities (CAT and POD) increased, accompanied by a moderate rise in malondialdehyde (MDA). Under I2, treatments enhanced LAI, grain yield, oil content, and soluble protein without significant changes in MDA. Under I3, zeolite and chitosan improved LAI, grain and oil yield, increased POD and CAT activities, and reduced MDA. Overall, applying zeolite (4.5 t ha⁻ 1 ) and chitosan (0.5%) effectively alleviated drought stress by enhancing physiological performance, yield, and antioxidant capacity. These results demonstrate the potential of zeolite and chitosan as sustainable solutions to improve drought tolerance in sesame cultivation, particularly in water-scarce environments.